The Use of Question, Answer, Relationship Strategies to Improve The Tenth-Grade Students’ Reading Comprehension At SMA Dwijendra Denpasar in The Academic Year 2022/2023 - Petronela Seraviana Yahni; I Gusti Ayu Indah Triana Juliari; I Komang Dedik Susila (Widya Accarya, 2024)
This research aims to improve the student’s reading comprehension of the narrative text using the Question Answer Relationship (QAR) strategy at SMA Dwijendra Denpasar. It was done through planning, action, observation, and reflection. This research was Classroom Action Research (CAR) consisting of two cycles. The subject of this research was 35 students of tenth grade SMA Dwijendra Denpasar in the academic year 2022/2023. The instrument in this research was a test (multiple choice). The test consists of a pretest and a post-test. The data were analyzed quantitatively to get the mean score and percentage. The result showed that there was an improvement in the student’s achievement in narrative text. Most of the students increased their scores gradually at the end of the cycle. The result of the mean score of students in the pretest was 60.14, the mean score in post-test 1 was 70.7, and the mean score in post-test 2 was 82. It can be concluded that the QAR strategy could improve the student’s reading comprehension of the tenth-grade students at SMA Dwijendra Denpasar.